(untitled) (American Journal of Islam and Society, 2017)
The Summer Institute for Scholars 2017, held at the IIIT headquarters in Herndon, VA, from July 26-29, brought together a group of scholars to address “Theologies and Ethics of Justice: New Directions for Islamic Thought in the 21st Century.” To present as many of their ideas as possible, the wideranging and thought-provoking comments of the chairs and discussants are not recounted The event began with welcoming remarks by Ermin Sinanović (program director and director of research, IIIT), Abubaker al-Shingieti (executive director, IIIT) and Hisham Altalib (president, IIIT). The participating scholars, students, and special guests were introduced and viewed a film on IIIT. The special panel on “Justice in Islamic Thought” was addressed by Ramon Harvey (Ebrahim College, London) and Jonathan A.C. Brown (Georgetown University; via Skype). Ramon Harvey’s paper, “The Qur’an and the Just Society: An Enquiry into Scriptural Theology, Ethics, and Hermeneutics,” introduced the theoretical framework of his forthcoming book, The Qur’an and the Just Society. He presented the basic underlying enquiry: the search for the meaning of societal justice within the Qur’anic worldview. His argument proceeded in three steps: (1) justice in the Qur’an must be situated within the broader “moral narrative” about the spiritual journey of souls and societies and from which an implicit moral theology can be detected; (2) that it is possible to build on such Qur’anic indications to articulate a theological and ethical system that models it; and (3) that such a system gives a meaningful epistemological foundation for a hermeneutics to discover the Qur’an’s basic principles of justice when contextualized within the initial Muslim community led by Prophet Muhammad ...